2022
DOI: 10.1093/nop/npac056
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Gamma Knife radiosurgery for cavernous sinus hemangiomas: A Chinese single-center retrospective study for 10 years of 187 patients

Abstract: Background Aim of this study is to retrospectively review the effectiveness and safety of personalized Gamma Knife radiosurgery (GKRS) for cavernous sinus hemangiomas (CSHs), summarise experience of personalized GKRS treatment for different volume of CSHs. Methods 187 CSHs patients who received personalized GKRS treatment in our center from 2011.1.1 to 2020.12.31 were enrolled in this study and classified into small and mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…associated with a previous attempt at surgical resection, likely a result of irreversible peroperative damage to surrounding cranial nerves. 22 Our data is consistent with existing observations that GKRS in CSH provides excellent longterm control, with symptomatic and neurological improvement. Six months after GKRS, the mean tumor volume reduction was 64.9%, with increasing volume reduction with greater follow-up (Figure 1).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 4 more Smart Citations
“…associated with a previous attempt at surgical resection, likely a result of irreversible peroperative damage to surrounding cranial nerves. 22 Our data is consistent with existing observations that GKRS in CSH provides excellent longterm control, with symptomatic and neurological improvement. Six months after GKRS, the mean tumor volume reduction was 64.9%, with increasing volume reduction with greater follow-up (Figure 1).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…29 Yang et al demonstrated that a personalized approach to GKRS in CSH, reserving staged procedures for large tumors resulted in 91.5% tumor volume reduction with complications in 3.7% of patients across a spectrum of 19 large and 23 giant CSH. 22 CyberKnife radiosurgery delivered as 21 Gy in three fractions or 22 Gy in four fractions also appears to be effective in giant CSH, producing 88% mean tumor reduction with no radiation-induced complications. 30 Hypofractionated GKRS was employed in two patients with giant CSH delivering five fractions of 5 Gy each.…”
Section: The Use Of Gamma Knife Radiosurgery In Large Cavernous Sinus...mentioning
confidence: 89%
See 3 more Smart Citations